(untitled) (Colombia Medica, 2012)
Introduction: The role of sentinel node biopsy has revolutionized breast cancer treatment. This determination reduces the mobility of a complete axillary lymphadenectomy. The aim of our study is to analyze the value of sentinel node in low-grade histological breast tumors, studied with hematoxylin and eosin techniques, Immunohistochemistry, and molecular chain reaction in real-time quantitative polymerase (RT-PCR). Materials and methods: In a pilot study we studied a total of 21 patients with histological diagnosis of mucinous carcinoma, adenoid cystic carcinoma, and medullar carcinoma that underwent the sentinel node technique. Once the lymph node was removed, it was sent to pathology, where it was fragmented and evaluated, using between 25% and 50% of the lymph node for molecular biology laboratory studies. Results: The sentinel nodes studied were 32, corresponding to the 21 patients. Of the 32 lymph nodes analyzed, 29 (90.6%) were negative on histopathological examination and the molecular identification, 2 (6.2%) were positive in both techniques and 1 (3.125%) lymph node was positive with quantitative RT-PCR and negative in histology (H&E), which – subsequently by immunohistochemistry (IHC) – was diagnosed as isolated tumor cells (ITC). Conclusion: When comparing the techniques of hematoxylin and eosin, immunohistochemistry, and molecular RT-PCR technique, we found greater sensitivity of molecular techniques; this can reduce the false negative and improve diagnosis of sentinel node metastases. Patients with low histological grade carcinomas have high survival rates, less aggressive tumor behavior, and reduced lymph node at diagnosis.